Development of DC Converter for Battery Charger of Light Electric Motorcycles - Pun, Chun Fai; Ahmad, Md Zarafi (Evolution in Electrical and Electronic Engineering, 2023)
The world has seen the rise of electric vehicles in recent decades and electrified two-wheeled transportation has slowly made it into the market as well. In this study, a DC/DC converter will be designed and developed with the assistance of MATLAB Simulink and produce a desired output according to set parameters that will be inputted into the system. One of the issues is that basic DC/DC converters can be rudimentary, and the outcome of that converter could be electric energy that is more unstable. Hence, a feedback control loop system such as a PID controller with fuzzy logic rules can be implemented to assist in stepping up or down electricity. Finally, the objectives to be reached are that the output of this converter shall be acquired through the simulation and to confirm that a feedback control loop system can assist in providing stable electricity for electric charging.